How to communicate better by discarding acronyms - Monge Nájera, Julián (Universidad de Costa Rica, 2023)
The scientific literature is plagued by unnecessary abbreviations specially acronyms, which hinder understanding. With current technology, most acronyms are no longer needed. Here I present a practical lesson of how to improve a scientific text by eliminating abbreviations.